Hepatoprotective Effect of San-Cao Granule on Con A-Induced Liver Injury in Mice and Mechanisms of Action Exploration - Yang, YuXue; Zhang, Ping; Wang, Yingying; Wei, Shizhang; Zhang, Lu; Wang, Jiabo; Lu, Xiaohua; Zhou, Houqin; Li, Ruisheng; Wen, Jianxia; Zhou, Xuelin; Li, Haotian; et al. (Frontiers in Pharmacology, 2018)
Objective: San-cao Granule (SCG), a traditional Chinese herb formula, has been used for treating autoimmune hepatitis (AIH) in our clinics for a long time. However, its active ingredients and mechanisms of action were still unknown due to its complicated chemical compositions. In the present study, the pharmacological study of SCG on acute liver injury induced by Concanavalin A (Con A) was performed to provide a scientific evidence for SCG against liver injury. Methods: In order to screen active components and predicate mechanisms of action, an “ingredients-target-disease” interaction network was constructed by network pharmacology. Then, the pharmacological study was performed to evaluate the therapeutic effect and the underlying mechanisms of SCG on Con A-induced liver injury in mice. Results: This research demonstrated the pharmacological effect of SCG on Con A-induced liver injury, which was through improving the liver function, relieving the pathological changes of liver tissue, decreasing the level of pro-inflammatory cytokines, thus balancing the pro and anti-inflammatory cytokines. And the anti-inflammatory of SCG may advantage over the Ursode-oxycholic acid (UDCA). Network pharmacology analysis revealed that the pharmacological effect of SCG might be related to its active ingredients of taraxanthin, dihydrotanshinone I, isotanshinone I, γ-sitosterol, 3β-acetyl-20,25-epoxydammarane-24α, and δ-7-stigmastenol. The hepatoprotective effect of SCG was reflected by suppressing Con A-induced apoptosis which was mediated by TRAIL and FASL. Conclusion: The combination of network pharmacology and experimental data has revealed the anti-apoptotic effect of SCG against Con A-induced liver injury.